Theoretical model for the formulation of digital marketing plans - González - Castro, Yolanda; Rebeca - Madariaga, Enilsa; Arciniégas - González, Gloria Amparo (Universidad Francisco de Paula Santander, 2022)
Digital marketing tools are diverse and are constantly updated, however, each economic sector and each company according to its characteristics must use a group of technologies in accordance to their needs, requirements and objectives. However, there are no models that can guide companies in the processes of planning digital marketing, additionally, small companies lack experts to guide the process. In this sense, documentary research with a qualitative approach was carried out in order to build a theoretical model to formulate digital marketing plans. The artisan sector was selected as the object of study. The results will allow its use in different organizations according to their planning needs.